Anarâškielâ postpositioi pelni já piälán čäällim sierâ já oohtân tievâdâsâinis SIKOR-tekstâčuágálduvâst - Petter Morottaja; Marja-Liisa Olthuis; Fabrizio Brecciaroli (Nordlyd: Tromsø University Working Papers on Language & Linguistics, 2022)
Inari Saami does not have a strong written tradition. The current orthography was adopted as recently as the 1990s, and the revitalization process is beginning only now to shift its focus from increasing the number of speakers to strengthening the literacy of the language. This article studies the Inari Saami postpositions pelni and piälán as well as their shorter forms peln/beln and pel/bel. The main question is whether these postpositions are joined to the noun preceding them or stand after it as separate words. The research is based on the SIKOR Inari Saami free corpus developed by the Giellatekno team. The postpositions have been analyzed semantically taking into account the frequency with which they occur in the literature. They have been divided into four semantic groups: 1) place, 2) orientation and direction, 3) time and 4) other semantic categories. The long forms pelni and piälán are mostly written as separate words – except for when they are used to express orientation or direction – whereas the short forms peln/beln and pel/bel are usually joined to the preceding word other than in time expressions. Alternative explanations for such variation are also discussed.